Analysis on Fiscal Capacity and Regional Financial Acceleration: A Case Study on Ternate City, Indonesia - Hadi Sirat, Abdul; Zam-Zam, Irfan; Muhammad, Zikri (International Journal of Engineering and Technology, 2018)
Indonesian Act No. 32 and 33 by 2014 about the formation of the regional autonomy is a challenge for local governments to utilize the potentials of the region. One of the local revenues for enhancing fiscal area is Regional Own Source Revenue (PAD), which are sourced from taxes and retributions. This research aims to analyze the financial management from the Government of Ternate. The secondary data collected from DPD, BPS, and offices related to the financial areas in 2010 – 2014 as well as data on the results of interviews with officials of the Regional Work Unit that has been appointed. By descriptive analysis, the result showed that economic growth has increased and indicated the increment of regional GDP. Based on the percentage of each sector against the Gross Domestic Regional Product in 2010 – 2014, trade, hotels and restaurants as well as other sectors were significantly contributing. The analysis found that the city of Ternate has not been financially able to carry out regional autonomy. However, the Government of Ternate is expected to improve regional financial capability by implementing intensification, the efforts to internally optimize local taxes and levies, and intensification, the efforts to expand and utilize new potentialities over regional tax and levies, to improve fiscal capability of the city of Ternate. To conclude, the effort in increase the District Own Source Revenue can be done by implementing intensification and intensification of regional tax and retribution.